POLITENESS RELATED TO GENDER PERSPECTIVES IN THE AMERICAN PRESIDENTIAL DEBATES - Adiyanti, Puput; Halim, Abdul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
In this study, the researcher discussed the use of Politeness in the first presidential debate between Hillary Clinton and Donald Trump, President Trump and former VP Biden Face Off in First Presidential Debate. In this study, the researcher aims to find out about the types of politeness used by the two debaters in the two debates and the differences in the use of politeness based on a gender perspective. In determining this, the researcher uses the theory of Brown and Levinson (1987) and Sara Mills (2003). In researching the problem the researcher used a qualitative descriptive method. The researchers found the use of politeness was found based on Brown and Levinson's theory and there were differences in the use of the four types of sub-strategies in the two debates like Bald on record (Showing disagreement, Give advice and Warning/Threatening), Positive politeness (Paying attention to listeners wants, Exaggerate, Include both S and H, Offer promises, Give an explanation, and Give gift to H), Negative Politeness (Be pessimistic, Give deference, Apologizing, Go on record), and Off Record (Give hints, Overstate, Use metaphor, Use of rhetorical questions, an Be incomplete). When it comes to a gender perspective, there are differences in their use, which can be seen in the first debate between Donald Trump and Hillary Clinton, where the use of politeness is a type of Positive Politeness, while the debate between Donald Trump and Joe Biden is mostly Bald on record.